Contextual Learning Through Social Experiments to Improve Students' Understanding in Learning Fikih - Ajat Hidayat; Sasmi Nelwati; Misra (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to examine how the effectiveness of contextual learning through social experiments can improve students' understanding. The method used is qualitative with a case study approach to see the phenomenon directly. The informants in this research were 12 informants, namely 1 fiqh teacher and 5 students at MTSN 4 Padang, as well as 1 fiqh teacher and 5 students at MTS An-Nur Padang. Data collection uses observation, interviews, and documentation which is then analyzed by reducing, presenting, and drawing conclusions. The results of this research prove that in general contextual learning through social experiments provides real experience to students and is proven to be able to increase students' understanding of the subject of jurisprudence, this can be seen from the fact that 80% or 24 of the 30 students in class VIII A at MTSN 4 Padang can complete the summative test with a score above the KKM, the same thing was also found in class VIII 1 MTS An-Nur Padang students where 80% or 16 out of 20 students had a score above the KKM, from this, it can be seen that after the students were given learning based on social experiments there is an increase in learning outcomes. From this research, the researcher concluded that creative learning will produce good results. Seeing as the main problem in education today is student boredom, this can be overcome with innovative learning such as contextual learning through social experiments.